THE ROLE OF EDUCATION IN INTEGRATING THE ECOLOGICAL VALUES OF THE QUR'AN : A THEMATIC STUDY OF VERSES ON THE ENVIRONMENT IN THE ERA OF GLOBAL CLIMATE CRISIS - Imam Anas Hadi; Kholil Baedowi; Raghusfi Bhuena Ventura; Mohamad Johan Saril; Dimas Sari Martasila (LP2M IAI Al-Khairat Pamekasan, 2026)
The global climate crisis is a multidimensional threat that not only impacts the natural ecosystem, but also the sustainability of human life. Various secular and technocratic approaches have been applied to overcome this crisis, but have not been able to touch the moral and spiritual roots of the problem. This article aims to examine the ecological values ​​in the Qur'an through a thematic interpretation approach (tafsīr al-mawḍū‘ī) to verses related to the environment, and to examine their relevance in responding to the challenges of the contemporary climate crisis. The results of the study show that the Qur'an contains transcendental ecological principles such as the concept of khalifah, mīzān (balance), the prohibition of fasād (damage), and the recommendation not to be excessive (isrāf), which function as the basis for Islamic environmental ethics. The integration of these revealed values ​​offers a new paradigm that can overcome the spiritual vacuum in conventional approaches. Thus, a religious approach based on the Qur'an has the potential to be a significant contribution in building collective ecological awareness and encouraging an environmentally friendly civilization.